Especialidades Tradicionales Garantizadas Made in Perú y la Propiedad Industrial como aliado en la reactivación del sector gastronómico - Manzur Filomeno, Karin Paola (Pontificia Universidad Católica del Perú, 2025)
In November 2021, DS 170-2021-PCM was enacted in Peru, approving the Regulations of the Protection Regime for Traditional Specialties Guaranteed and the Geographical Indications Regime. By May 2023, the Directorate of Distinctive Signs (DDS) of Indecopi granted the registration of the first Traditional Specialty Guaranteed (TSG) in Peru, and the second in Latin America: El Pan de Anís de Concepción. During the first quarter of 2024, the Traditional Specialty Guaranteed seal was published on the Peruvian State’s single digital platform. As can be seen, TSGs are a new legal figure in Peruvian Industrial Property legislation. The purpose of this article is to present, in an educational way, the relevant information that allows to know, with the necessary detail, the most notable aspects of the applicable legal framework. It also highlights the great potential they must contribute to strengthening the national gastronomic market.

En noviembre de 2021, se promulgó en Perú el DS 170-2021-PCM, mediante el cual se aprobó el Reglamento del Régimen de Protección de las Especialidades Tradicionales Garantizadas y del Régimen de las Indicaciones Geográficas. Para mayo de 2023, la Dirección de Signos Distintivos (DSD) del Indecopi concedió el registro de la primera Especialidad Tradicional Garantizada (ETG) del Perú, y la segunda en Latinoamérica: el Pan de Anís de Concepción. Durante el primer trimestre de 2024, se publicó en la plataforma digital única del Estado peruano el sello de Especialidad Tradicional Garantizada. Como puede apreciarse, las ETG son una figura jurídica nueva en la legislación peruana de Propiedad Industrial. La finalidad de este artículo es exponer de modo didáctico la información relevante que permita conocer, con el detalle necesario, los aspectos más destacables del marco jurídico aplicable; poniendo además en evidencia el gran potencial que tienen para aportar en el fortalecimiento del mercado gastronómico nacional.
Traditional Specialities Guaranteed Made in Peru and Industrial Property as an ally in the reactivation of the gastronomic sector
Keywords: Industrial Property; Gastronomy; Tradition; Quality; Economic reactivation; Protection regime of TSG; Propiedad Industrial; Gastronomía; Tradición; Calidad; Reactivación económica; Régimen de Protección de ETG; https://purl.org/pe-repo/ocde/ford#5.05.00